Cytokine expression and signaling in drug-induced cellular senescence - Novakova, Z; Hubackova, S; Kosar, M; Janderova-Rossmeislova, L; Dobrovolna, J; Vasicova, P; Vancurova, M; Horejsi, Z; Hozak, P; Bartek, J; Hodny, Z (Oncogene, 2010)
Cellular senescence guards against cancer and modulates aging; however, the underlying mechanisms remain poorly understood. Here, we show that genotoxic drugs capable of inducing premature senescence in normal and cancer cells, such as 5-bromo-2'-deoxyuridine (BrdU), distamycin A (DMA), aphidicolin and hydroxyurea, persistently activate Janus kinase-signal transducer and activator of transcription (JAK/STAT) signaling and expression of interferon-stimulated genes (ISGs), such as MX1, OAS, ISG15, STAT1, PML, IRF1 and IRF7, in several human cancer cell lines. JAK1/STAT-activating ligands, interleukin 10 (IL10), IL20, IL24, interferon gamma (IFNgamma), IFNbeta and IL6, were also expressed by senescent cells, supporting autocrine/paracrine activation of JAK1/STAT. Furthermore, cytokine genes, including proinflammatory IL1, tumor necrosis factor and transforming growth factor families, were highly expressed. The strongest inducer of JAK/STAT signaling, cytokine production and senescence was BrdU combined with DMA. RNA interference-mediated knockdown of JAK1 abolished expression of ISGs, but not DNA damage signaling or senescence. Thus, although DNA damage signaling, p53 and RB activation, and the cytokine/chemokine secretory phenotype are apparently shared by all types of senescence, our data reveal so far unprecedented activation of the IFNbeta-STAT1-ISGs axis, and indicate a less prominent causative role of IL6-JAK/STAT signaling in genotoxic drug-induced senescence compared with reports on oncogene-induced or replicative senescence. These results highlight shared and unique features of drug-induced cellular senescence, and implicate induction of cancer secretory phenotype in chemotherapy.
Keywords: signální transdukce; Signal Transduction; Distamycins; transkripční faktor STAT1; Humans; HeLa buňky; Bromodeoxyuridine; interferony; stárnutí buněk; cytokiny; Interleukin-6; Drug Synergism; Interleukin-10; distamyciny; polymerázová řetězová reakce s reverzní transkripcí; Blotting, Western; Interleukin-8; interleukin-8; lidé; Interferons; Reverse Transcriptase Polymerase Chain Reaction; synergismus léků; Janus kinasa 1; bromodeoxyuridin; HeLa Cells; interleukin-6; interleukiny; Cytokines; RNA Interference; nádorové buněčné linie; Interleukins; Cellular Senescence; interleukin-10; Cell Line, Tumor; western blotting; STAT1 Transcription Factor; Janus Kinase 1; RNA interference